Short Term Outcome of Off Pump Coronary Artery Bypass Grafting in Patients with Low Ejection Fraction - Salekin, Mohammad Serajus; Sazzad, Md Faizus; Nahian, Syed Al; Mohammad Musa, Sumsul Arif; Alam, Mohammed Rabbikul; Choudhury, Dewan Iftakher Raza; Adhikary, Asit Baran (University Heart Journal, 2019)
Coronary artery disease is increasing in developing countries. Revascularization surgery in such patients with amenable coronary anatomy is a valid option. Coronary artery bypass grafting in patients with low ejection fraction (EF <35%) is very challenging although it is performing successfully in department of Cardiac Surgery of Bangabandhu Sheikh Mujib Medical University now a days. The purpose of this study is to evaluate the safety and effectiveness of off pump coronary artery bypass grafting for EF e”35% and EF <35% and also to compare between pre and postoperative echocardiographic findings in this two groups. The preoperative, at discharge, 1 month and 3 month postoperative follow up data of total 60 patients in two groups ( EF e”35% and <35%) who underwent isolated off pump coronary artery bypass grafting between July 2012 – June 2014 was evaluated. In group 1 preoperative LVIDd and LVIDs was 54.86±3.45 mm and 45.23 ±4.13mm and LVEF was 42.7±4.66. Postoperatively at 3 month follow up the LVIDd 45.43±5.03 mm, LVIDs 34.7±5.33 mm and LVEF 53.46±5.06. The improvement of mean LVIDd and LVIDs is statistically significant (p<0.001) and (p<0.05) respectively. But improvement of LVEF is not statistically significant (p>0.05). Similarly in group 2 patients preoperative LVIDd, LVIDs and LVEF is 67.06±3.67mm, 59.1±4.35mm and 29.26±4.25. Postoperatively at 3 months follow up of this group the LVIDd, LVIDs and LVEF is changed to 57.56±4.96 mm, 48.3±5.53 mm and 38.93±6.03. The improvement of mean LVIDd and LVIDs is statistically significant (p<0.001) and (p<0.05) respectively. And the improvement of LVEF is also statistically significant (p<0.001). Significant improvement in terms of CCS grade and NYHA class was also observed specially in <35% ejection fraction group at 3moths follow up. We concluded that off pump coronary artery bypass grafting can be safely performed to the patients with normal and poor left ventricular ejection. Hence we recommended that off-pump CABG can be safely carry out in case of <35% ejection fraction patients. University Heart Journal Vol. 14, No. 2, Jul 2018; 53-61